Severe Lower Gastrointestinal Bleeding Due to Choriocarcinoma with AVM to the Ileum: A Case Report - Hasanzadeh, Malihe; Jahani, Najmeh; Khoroushi, Farzaneh; Sharifi, Nourieh (Current Women's Health Reviews, 2023)
Background: Choriocarcinoma and other placental tumors are rare, and metastasis to the gastrointestinal, especially the small bowel, is extremely rare. Furthermore, about 5% of all metastasis belongs to the GI tract. Case Presentation: We reported an 18 -year-old patient with severe GI bleeding. Serum BHCG level was 57322 mIU/mL. CT angiography and Pelvic MRI suggested a metastatic arteriovenous malformation to the small bowel. In surgery, we detected the AVM from the right side of the uterus to the ileum, and pathological findings confirmed the choriocarcinoma with metastatic AVM to the ileum. Conclusion: Chemotherapy started after surgery, and the patient was asymptomatic on follow-up after 14 months. The results showed that GTN was a differential diagnosis when patients are referred with these signs and symptoms.
Keywords: gestational trophoblastic neoplasia